Genetic Diversity in Aromatic Rice Varieties and Molecular Insights into BADH2 Gene Variability - Bairwa, Rakesh Kumar; Kushwaha, Amarkant; Mohan, Shiva; Kumar, Sandeep; Gupta, Arun; Kamble, Umesh R; Sharma, Amit Kumar (Journal of Cereal Research, 2025)
Aromatic rice is a very popular variety of rice that is renowned for its distinctive aroma, exceptional cooking qualities and nutritional attributes. These rice varieties are indigenous to the foothills of the Himalayas, which is considered the centre of diversity for aromatic rice. India boasts a diverse range of aromatic rice landraces, including the world-renowned Basmati rice. The fragrance of aromatic rice is an important quality trait, and it has been discovered that a compound called 2-acetyl-1-pyrroline (2AP) is responsible for it. The non-functional BADH2 gene leads to the accumulation of this compound in rice. Since the discovery of the BADH2 gene, several allelic variants have been identified across different germplasms from various countries. Molecular markers have been developed to screen these allelic variants and select for aroma in the early stages of the breeding program. This article provides a comprehensive understanding of the aroma pathway in rice and highlights the allelic variations of the BADH2 gene and the functional markers developed for breeding programs. The information presented here is essential for researchers and breeders working on aromatic rice breeding programs to develop new and improved varieties that can meet the increasing demand for aromatic rice worldwide.